Sexual harassment and abuse in sport: the role of the team doctor. Issue 13 (14th December 2011) - Marks, Saul; Mountjoy, Margo; Marcus, Madalyn
Abstract : Sexual harassment and abuse occur in all sports and at all levels with an increased risk at the elite level. The physical and psychological consequences of sexual harassment and abuse are significant for the athlete, their team and for the health and integrity of sport in general. The sports medicine health professional has an integral role to play in the prevention of sexual harassment and abuse in sport. This paper provides sport healthcare professionals with a practical guide on prevention strategies and advice on the recognition and management of suspected abuse.